The Elements Determining the Prevailing State of Poverty among Sea Food Harvesting Community along the North Eastern Coastal Belt of Sri Lanka - Umashankar, K.; Shalton, R.A. (Faculty of Agriculture University of Jaffna, Sri Lanka, 2018)
Mullaitivu is one of the districts located along the North Eastern coastal belt of Sri Lanka, relatively more viable for fishing industry. Before civil unrest, times were quite prosperous for the people of Mullaitivu. The thirty years of civil commotion dismantled and destroyed the social structure and the infrastructure. Presently, as the people return to their ancestral land, they are faced with a hostile climate and non-climatic factors such as the use of illegal fishing equipment, poaching, and over harvesting, etc. A radical change in the life style of rural folk, whose living was more in keeping with nature, could be another cause for their regression. The net result being that they do not harvest a return proportionate to the time, labour and the capital invested. Thus, these people are caught up in a whirl pool of poverty from which they are unable to emerge. Hence this research attempted to find out the socio-economic elements determining the contemporary state of affairs of the sea food harvesting community of the Mullaitivu District. A total of 192 fishing households were selected using purposive random sampling method. The poverty levels of the respondents were assessed based on the Multidimensional Poverty Index in compliance with UNDP HDRO standards. Using the Binary Response Logistic Model, an effort was made to decipher what community base or socio-economic characteristics were responsible for their state of poverty. It was found that membership in fishermen organization, income generated from fishing activity and income diversification practices of heads of households influenced poverty negatively at 1%, 5% and 5% significant levels, respectively, whereas, social interaction activity contributed positively towards poverty at 1% significant level. It is recommended by the researchers that the activity which influences poverty positively be discouraged and that which influences negatively be encouraged and fostered.
Keywords: Extension program; Fisheries; Logistic model; Mullaitivu; Poverty